2022
DOI: 10.1038/s41598-022-26986-2
|View full text |Cite
|
Sign up to set email alerts
|

FMR1 deletion in rats induces hyperactivity with no changes in striatal dopamine transporter availability

Abstract: Autism Spectrum Disorder (ASD) is a pervasive neurodevelopmental disorder emerging in early life characterized by impairments in social interaction, poor verbal and non-verbal communication, and repetitive patterns of behaviors. Among the best-known genetic risk factors for ASD, there are mutations causing the loss of the Fragile X Messenger Ribonucleoprotein 1 (FMRP) leading to Fragile X syndrome (FXS), a common form of inherited intellectual disability and the leading monogenic cause of ASD. Being a pivotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
(79 reference statements)
2
2
0
Order By: Relevance
“…Noteworthy, both WT and KO rats demonstrated reduced levels of motor activity due to the longer exposure and subsequent familiarity with the open-field apparatus. In agreement with our results, increased motor activity as deduced by the total time spent in the open-field apparatus was observed for Fmr1 KO compared to WT rats [ 38 , 39 ]. Another study [ 40 ] reported that KO rats were hyperactive, only during the first recording interval.…”
Section: Discussionsupporting
confidence: 92%
“…Noteworthy, both WT and KO rats demonstrated reduced levels of motor activity due to the longer exposure and subsequent familiarity with the open-field apparatus. In agreement with our results, increased motor activity as deduced by the total time spent in the open-field apparatus was observed for Fmr1 KO compared to WT rats [ 38 , 39 ]. Another study [ 40 ] reported that KO rats were hyperactive, only during the first recording interval.…”
Section: Discussionsupporting
confidence: 92%
“…Noteworthy, both genotypes demonstrated reduced levels of motor activity due to the longer exposure and subsequent familiarity to the open eld apparatus. In agreement with our results, increased motor activity as deduced by the total time spent in the open eld apparatus was observed for Fmr1 KO compared to WT rats [ 35,36 ].In another study [ 37 ],reported that KO rats were hyperactive, only during the rst recording interval. On the other hand, previous studies have shown either no change [ [38][39][40] or a reduction in spontaneous motor activity compared to the WT counterparts [ 8,41 ].…”
Section: Discussionsupporting
confidence: 91%
“…The elevated plus maze (EPM) apparatus comprised two open (50 × 10 × 40 cm; l × w × h) and two closed arms (50 × 10 × 40 cm; l × w × h) that extended from a common central platform (10 × 10 cm). The test was performed as previously reported ( Manduca et al, 2015 ; D’Elia et al, 2022 ). At PND 35, rats were individually placed on the central platform of the maze for 5 min.…”
Section: Methodsmentioning
confidence: 99%